2018
DOI: 10.4149/neo_2018_181212n476
|View full text |Cite
|
Sign up to set email alerts
|

Trichostatin A inhibits proliferation of triple negative breast cancer cells by inducing cell cycle arrest and apoptosis

Abstract: Triple negative breast cancer (TNBC) is the most aggressive subtype of breast cancer with poor outcome. Because of lacking therapeutic targets, chemotherapy is the main treatment option for patients with TNBC. Overexpression of HDACs correlates with tumorigenesis, highlighting the potential of HDACs as therapeutic targets for TNBC. Here we demonstrate that trichostatin A (TSA, a HDAC inhibitor) selectively inhibits the proliferation of TNBC cell lines HCC1806 and HCC38 rather than a normal breast cell line MCF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Since ZEB1 is a transcriptional factor that is not easily druggable, indirectly inactivating ZEB1 by TSA open a new window for resistant TNBC. Notably, instead of directly affecting cyclinD1, CDK4/6, and BCL-XL [ 43 ], we found that co-treatment with TSA and chemotherapeutic drugs could synergistically inhibit cell viability by inducing apoptosis, which is clearly mediated by CHFR. In patients with breast cancer, CHFR was found to positively correlate with poor survival (both mesenchymal and basal-like 1 malignant breast cancer).…”
Section: Discussionmentioning
confidence: 99%
“…Since ZEB1 is a transcriptional factor that is not easily druggable, indirectly inactivating ZEB1 by TSA open a new window for resistant TNBC. Notably, instead of directly affecting cyclinD1, CDK4/6, and BCL-XL [ 43 ], we found that co-treatment with TSA and chemotherapeutic drugs could synergistically inhibit cell viability by inducing apoptosis, which is clearly mediated by CHFR. In patients with breast cancer, CHFR was found to positively correlate with poor survival (both mesenchymal and basal-like 1 malignant breast cancer).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cyclin D1 was found to be overexpressed in breast cancer tissues, suggesting that it may serve as a potential biomarker (31). A number of studies have indicated that the suppression of cyclin D1 may inhibit breast cancer cell proliferation (32)(33)(34). Furthermore, the forced expression of HSF1 has been shown to increase the expression of cyclin D1 (35).…”
Section: Discussionmentioning
confidence: 99%
“…The same year, Song et al reported a study in which the inhibition of TNBC by trichostatin A (TSA), an HDACI, was investigated [ 67 ]. The experimental findings indicated that TSA treatment results in decreased expression of CYCLIN D1, CDK4, CDK6, and BCL-XL, but increased P21 expression.…”
Section: Resultsmentioning
confidence: 99%
“…SAHA managed to inhibit effectively the growth of TNBC cells. The combinations of OBP-801 with eribulin and TSA with doxorubicin led to promising therapeutic strategies, through synergistic action with other agents such as olaparib, entinostat, and eribulin [ 65 , 66 , 67 , 68 , 69 ]. They induce apoptosis and inhibit angiogenesis.…”
Section: Discussionmentioning
confidence: 99%